Legal Protection for Consumers of Life Insurance Products During COVID-19 Pandemic in Indonesia - Fausia Isti Tanoso (Global Legal Review, 2022)
Despite life insurance penetration rate has increased from year to year and the total premium income of the life insurance industry had reached trillions of Indonesian Rupiah by the end of 2020, it is undeniable that legal protection for consumers of life insurance products still has its shortcomings. This can be seen from the issuance of Law Number 8 of 1999 concerning Consumer Protection, in which its issuance was more or less influenced by the International Monetary Fund (IMF) during the 1998 monetary crisis. In contrast, regulation related to insurance has been stipulated decades before Indonesia’s independence through Kitab Undang-Undang Hukum Dagang (KUHD / Wetboek van Koophandel voor Indonesie) or the Indonesia Commercial Code. Adetailed regulation regarding life insurance was introduced through Law Number 2 of 1992 concerning Insurance Business which focuses on insurance companies and their supporting institutions. However, there was no specific regulation regarding protection for insurance consumers until 2013 when Financial Services Authority (OJK) issued Regulation Number 1/POJK.07/2013 concerning Consumer Protection in the Financial Services Sector which regulates consumer protection not only for insurance company, but also for other financial institutions including banks, securities company, investment advisor, pension fund, and financing company. Later, the Government of Indonesia (GoI) issued Law Number 40 of 2014 concerning Insurance in which, according to its elucidation, reflected great attention and support to protect consumers of insurance services. In 2020 during the global COVID-19 pandemic, the financial services sector was greatly affected and consequently, the condition also affected how insurance companies interact with their consumers due to some restrictions during the pandemic. In this regard, this study attempts to analyze regulations issued by GoI during COVID-19 related to consumer protection of life insurance products, within the scope of Law Number 8 of 1999, OJK Regulation Number 1/POJK.07/2013, and Law Number 40 of 2014.